TOEFL Essentials: Effective Training to Master Grammar and Structure for Students - Sri Astuti Nasir; Rostina; Iswardhani, Indri; Windarsari, Wiwin Riski; Sandira, Nur Fadilah Ayu (Yayasan Zia Salsabila, 2025)
The TOEFL preparation training program conducted for students aimed to enhance their proficiency in key areas of TOEFL, with a particular focus on grammar and structure. The training utilized a pretest-posttest design, where a pretest was administered to assess students' initial skills, followed by targeted lessons on basic grammar concepts, sentence structure, the use of